2019
DOI: 10.2196/12869
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mental Health Interventions for Depression, Anxiety, and Enhancement of Psychological Well-Being Among College Students: Systematic Review

Abstract: Background College students are increasingly reporting common mental health problems, such as depression and anxiety, and they frequently encounter barriers to seeking traditional mental health treatments. Digital mental health interventions, such as those delivered via the Web and apps, offer the potential to improve access to mental health treatment. Objective This study aimed to review the literature on digital mental health interventions focused on depression, anxie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
380
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 537 publications
(411 citation statements)
references
References 149 publications
(624 reference statements)
19
380
0
12
Order By: Relevance
“…A meta-analysis of 17 trials of 1,480 participants showed that computerized and web-based intervention were effective at reducing depression and anxiety compared with inactive control ( 4 ). A systematic review of 89 studies demonstrated that nearly 81% of digital mental health programs are effective or partially effective at reducing a variety of symptoms of common mental disorders and improving well-being ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 17 trials of 1,480 participants showed that computerized and web-based intervention were effective at reducing depression and anxiety compared with inactive control ( 4 ). A systematic review of 89 studies demonstrated that nearly 81% of digital mental health programs are effective or partially effective at reducing a variety of symptoms of common mental disorders and improving well-being ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of digital mental health programs in college populations has been established. A systematic review found that the majority of digital mental health interventions for college students were effective in producing changes in psychological outcomes, such as depression and anxiety, yet few of the tested programs were publicly available and fewer were delivered via apps [ 3 ]. In addition, the vast majority of college students own smartphones, making apps a potentially accessible option to deliver services [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…One promising approach is to provide self-help resources that students can access on their own, privately, whenever is convenient. Such self-guided resources have been found to be effective for college students (Lattie et al, 2019) and to be of interest to students, including those who otherwise might not seek services (Levin, Krafft & Levin, 2018). Research in this area has primarily focused on web and mobile programs, which theoretically is highly scalable due to minimal cost per end user once the platform is developed.…”
mentioning
confidence: 99%